Propriedades ópticas de filmes semicondutores GaAsBi e GaSbBi - De Souza, Daniele (2022)
Bismuth-diluted III-V are interesting materials for possible applications in optoeletronic and spintronic devices. If we add a small amount of Bi in III-V materials, we observe a strong reduction in the band gap energy. In addition, it is expected that these materials present an important attenuation of Auger recombination for Bi concentrations higher than 10%. Therefore, these materials are good candidates for the development of optoelectronic devices in the near-infrared region. In this work, we have performed a systematic study of III-V materials with different Bi concentrations grown by molecular beam expitaxy (MBE) in different substrates. Particularly, we have investigated films GaSb(1-x) Bix grown on (100) GaSb substrates and n- and p-doped GaAs(1-x) Bix films grown on (100) and (311)B GaAs substrates. The GaSb(1-x) Bix films were investigated using high resolution XRD (HRXRD), AFM and Raman spectroscopy. We have observed that the GaSb(1-x) Bix films have a good crystalline quality. In addition, we have observed several Raman modes associated with GaSb, Bi clusters and GaBi. We have observed an important increase of Raman intensity depending on the Bi concentration and laser wavelength. This result was attributed to the resonant Raman effect. We have also investigated the GaAsBi samples using different techniques such as: HRXRD, Raman and low temperature photoluminescence (PL). We have observed that the incorporation of Bi in the n- and p-type doped samples were similar. However, these samples have shown important difference in the density of structural defects and non-radiative centers. This result indicates that the density of defects depends on the type of doping in GaAs(1-x) Bix and on the substrate orientation. In addition, we have observed that the sample grown on the GaAs (100) substrate has a compressive strain 2.7 times higher than the samples grown on the substrate GaAs (311)B. In general, our results evidence that both the amount of compressive strain and the density of defects depend on the substrate orientation and type of doping, which affects considerable the optical properties of GaAsBi thin films.